THE EFFECTIVENESS OF WEB-BASED INSTRUCTION ON WRITING SKILL OF ENGLISH DEPARTMENT STUDENTS OF FKIP RIAU UNIVERSITY (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This quasi-experimental research aims to test the effectiveness of teaching writing by using web-based instruction on writing skills of English Department students of Teacher Training and Education Faculty (FKIP)Riau University.The formulation of theproblemto beaddressed is: Is there any effectiveness of web-based instruction on writing skills of English Department students of FKIPRiau University? The research was conducted at English Department ofFKIP Riau University during odd semester 2014-2015. Cluster sampling technique was used to select two classes of students to become the sample of this research. One class of students was used for experimental class and another one was used as a control class. Students in the experimental class were taught by using web-based instruction methodand students in the control class were taught by using conventional method. Instrument used in this research was a writing test and the data were analyzed by using SPSS version 19.0.The finding showed thatweb-based instruction was effectively improved the studentsâ writing ability.Key words:web-basedinstruction, writing skill